ANALISIS STUDI KARAKTERISTIK PARKIR (Studi Kasus RS. Dr. Muwardi, Swalayan Matahari Purwosari, Kampus UMS di Surakarta) - Suwardi, Suwardi (Jurnal Teknik Sipil ITENAS, 2007)
Dr. Moewardi Hospital is a hospitalÂ owned by Surakarta Regional Government, UMS Campus is a largest private university of Surakarta, and Matahari Plazais the largest plaza of Surakarta recently, all of the are needs the comportable parking area. To anticipate the parking area problem, it needs the research about the characteristics about the parking area of Dr. Moewardi Hospital, Matahari Plaza, and UMS Campus. The researcher used the descriptive analytic to accomplish the research. From the research result, itâ€™s expected as the reference and developingÂ every activity. With the ratio as 15 minutes for 11.5 hours, based from the analysis results it may concluded that the highest accumulation of car parking in Dr. Moewardi Hospital 168 cars which over the parking index as 124%, in UMS campus as 101 cars, with the parking index as 63%, and Matahari Plaza 92 cars with the parking index as 73%. Parking turn over in Dr. Moewardi Hospital as 4,11 UMS as 2,68 and Matahari Plaza as 5,29. The highest accumulation of motor find in Dr. Moewardi Hospital at 421 with parking index as 112, UMS as 771 cars with parking index as 107 and Matahari Plaza as 124 cars, parking index 77%. Parking turn over of motor of Dr. Moewardi Hospital 4,05, UMS Campus as 2,57 and Matahari Plaza as 7,10. The parking area for motors and cars of Dr. Moewardi Hospital is need to widening, and the parking area for motors of UMS Campus is needs to widening.